Detection of Mycobacterium Tuberculosis Resistance to Pyrazinamide Antibiotic Using Polymerase Chain Reaction (PCR) Technique - Edy Kurniawan; Idham Halid (Jurnal Biologi Tropis, 2022)
The tuberculosis treatment control program is constrained by the outbreak of TB that is resistant to anti-tuberculosis drugs (OAT), especially multidrug-resistant tuberculosis. Confirmation of tuberculosis drug resistance really needs to be done in each area considering that there are variations in phenotypes and genotypes in each region through laboratory tests such as molecular biology tests. Aim of study to determine the prevalence of Mycobacteriumtuberculosis resistance to pyrazinamide antibiotics by PCR technique. This research is a descriptive exploratory study which has been carried out in the molecular biology laboratory of West Nusa Tenggara Provincial Public Hospital. The sample in this study was positive TB sputum obtained from Patut Patuh Patju Hospital The Province of West Nusa Tenggara. The results showed that 5 of the samples were pyrazinamide resistant. Concluded that Resistance to pyrazinamide antibiotics was found from 10 samples, 5 of which had developed resistance to pyrazinamide antibiotics.